Pharmacokinetics of Drug Absorption and Metabolism: Mechanisms, Influencing Factors, and Screening Strategies in Drug Development - Shams, Wajihus; Acharya, Monika; Jacob, Rosmin; Jaiswal, Riya; Renulata, Renulata; Murtaza, Muhammad; Juyal, Chhavi; Kumar, Akash; Yusuf, Shehu; Azeem, Mohd. Umar; et al. (Journal of Neonatal Surgery, 2025)
The pharmacokinetics of drug absorption and metabolism play a crucial role in determining therapeutic efficacy and safety. Drug absorption, primarily occurring in the small intestine, is influenced by various physicochemical and physiological factors, including solubility, particle size, gastrointestinal motility, and metabolic enzyme activity. The intestinal epithelium serves as both an absorption site and a barrier, impacting oral drug bioavailability through first-pass metabolism involving Phase I and Phase II reactions. Following absorption, drugs undergo distribution, metabolism, and excretion, with the liver being the primary site of biotransformation, largely mediated by the cytochrome P450 (CYP450) enzyme system. Understanding drug metabolism is critical for pharmaceutical development, particularly in predicting drug interactions and toxicity. This review explores key mechanisms, influencing factors, and screening strategies used in drug absorption and metabolism studies, emphasizing their significance in drug discovery and regulatory sciences.